Traces and determinants of pseudodifferential operators - Scott, Simon (Simon Gareth) (Oxford : Oxford University Press, 2010)
For graduates and researchers in mathematics and physics 'Traces and Determinants of Elliptic Pseudodiff Operators' covers the basics of the topics, advances and developments.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Pseudodifferential operators; Elliptic operators